Contributing factors to change-of-direction ability in professional rugby league players - Delaney, J. A.; Scott, T. J.; Ballard, D. A.; Duthie, G. M.; Hickmans, J. A.; Lockie, R. G.; Dascombe, B. J. (The Journal of Strength and Conditioning Research, 2015)
Rugby league is an intermittent team sport in which players are regularly required to accelerate, decelerate, and change direction rapidly. This study aimed to determine the contributing factors to change-of-direction (COD) ability in professional rugby league players and to validate the physical and physiological components of a previously proposed COD ability predictor model. Thirty-one male professional rugby league players (age: 24.3 ± 4.4 years; height: 1.83 ± 0.06 m; body mass: 98.1 ± 9.8 kg) were assessed for anthropometry, linear speed, various leg muscle qualities, and COD ability. Change-of-direction ability was assessed for both the dominant (D) and nondominant (ND) legs using the 505 test. Stepwise multiple regression analyses determined the combined effect of the physical and physiological variables on COD ability. Maximal linear speed (SpMax) and relative squat strength (squat:BM) explained 61% of the variance in 505-D performance, whereas measures of mass, unilateral, and bilateral power contributed 67% to 505-ND performance. These results suggest that the 505-ND task was heavily dependent on relative strength and power, whereas the 505-D task was best predicted by linear sprint speed. Second, the physical component of the COD predictor model demonstrated poor correlations (r = -0.1 to -0.5) between absolute strength and power measures and COD ability. When made relative to body mass, strength and power measures and COD ability shared stronger relationships (r = -0.3 to -0.7). Change-of-direction ability in professional rugby league players would be best improved through increases in an athlete's strength and power while maintaining lean muscle mass.